If it's not what You are looking for type in the equation solver your own equation and let us solve it.
52+x=65
We simplify the equation to the form, which is simple to understand
52+x=65
We move all terms containing x to the left and all other terms to the right.
+1x=+65-52
We simplify left and right side of the equation.
+1x=+13
We divide both sides of the equation by 1 to get x.
x=13
| 5/9x3/10 | | 24/1 | | 3x+26+6x+5=360 | | 4.3=x+3 | | 6x-3+2x=5x+9 | | X+29=48 | | 62.1=(20+.5x)+.15(20+.5x) | | M+9=12m-8m+21 | | 24-3w=7w+64 | | 2(-2b+5)-5b=-20+6b | | -(-2w-31)=30 | | -9(4x-2)=108-16 | | (a^3-2a^2)-(3a^2-4a^2)= | | 100000=x-.08x-260000 | | (X-2)-2(x-1)=(x+1)-(x-6) | | 46=47+1x | | cos(3x)=10x^2 | | 1260/m=20 | | 1260/m=20 | | 7x+5=8-x | | 2x+0.2=x-3 | | 80h-2=15 | | 2(x-6)=7x | | 80h-2= | | 12=z-5/3 | | 10a-3a=8+8a | | 2x+1=81 | | 12=z-5/4 | | 36x^2+24x-13=0 | | 22=6x^2+5x+1 | | 80-2=15f | | -4x-13=27 |